Localization of nucleocapsid (NP) antigenic sites by using a panel of monoclonal antibodies against the recombinant NP of Newcastle disease virus - Ahmad Raus, Raha; Ali, Abdul Manaf; Tan, Wen Siang; Mohd. Salleh, Hamzah; Eshagi, Majid; Yusoff, Khatijah (2007)
Three different NP antigenic sites were identified using deleted truncated NP mutants purified from Escherichia coli. One of the antigenic sites was located within amino acids 441 to 489 of C-terminal. Two other antigenic sites located within the Nterminal of NP protein from amino acids 26 to 121 and 122 to 375 residues. Identification of NP antigenic sites not only elucidates the NP sequences that are responsible in eliciting immune response, indirectly it also revealed which sequences are exposed on the NP herringbone-like structure.